The contamination of microplastics in China's aquatic environment: Occurrence, detection and implications for ecological risk. (1st March 2022) - Zhang, Ziqi; Gao, Shu-Hong; Luo, Gaoyang; Kang, Yuanyuan; Zhang, Liying; Pan, Yusheng; Zhou, Xu; Fan, Lu; Liang, Bin; Wang, Aijie
Abstract: The widespread occurrence of microplastics in aquatic ecosystems that resulted in environmental contamination has attracted worldwide attention. Microplastics pose a potential threat to the growth and health of aquatic organisms, thereby affecting the function of the ecosystems. As one of the top ten countries producing and consuming plastic products globally, China's aquatic ecosystems have been profoundly affected by microplastics. In this review, we have summarized the microplastics contamination in three typical water environments (marine environment, freshwater environment, and wastewater treatment plants) in China, elaborated on the adverse impacts of microplastics on the ecological environment, and evaluated the potential ecological risks exposed to the ecosystem. In addition, the progress of microplastics extraction methods, as the important basis of microplastics related research, in aquatic ecosystems was introduced, especially the difference between the extraction of microplastics from wastewater and sludge samples. At present, most of the research on microplastics focuses on "one point", such as a certain river or wastewater treatment plant. Research on the mitigation and transfer of microplastics among different connected water environments is still lacking. Also, the microscale ecotoxicity caused by microplastics is poorly understood. In the end, we proposed suggestions and perspectives for future research regarding microplastics in the aquatic ecosystems in China. Graphical abstract: Image 1 Highlights: The microplastics contamination situation in China was summarized on a global scale. The migration of microplastics in connected water environments was reviewed. The extraction of microplastics in sludge is more difficult. The ecological impact of microplastics should be paid more attention.